How the DIS3 proteins shape the human transcritpome - Costa, Paulo (2017)
The final step of eukaryotic mRNA degradation proceeds in either a 5’-3’ direction, catalyzed by XRN1, or in a 3’-5’ direction catalyzed by DIS3, DIS3L1 (the catalytic subunits of the exosome) and/or DIS3L2 (exosome-independent). Important findings over the last years have shed a new light onto the mechanistic details of RNA degradation by these exoribonucleases. In addition, it has been shown that they are involved in growth, mitotic control and important human diseases, including cancer. With the aim of analyzing how DIS3, DIS3L1 and DIS3L2 regulate the human transcriptome, each one of these nucleases was depleted by RNA interference in HeLa cells and levels of several reporter mRNAs was monitored by RT-qPCR. Our results show that these exoribonucleases are target specific and not directly involved in a particular mRNA surveillance mechanism. In parallel, our bioinformatics analysis of available transcriptomic data from cells depleted of DIS3L1, DIS3L2, XRN1, or UPF1 (which has a central role in nonsense-mediated mRNA decay) has shown some, but not full, redundancy among the transcripts regulated by these nucleases, which supports our experimental data. Presently, we are exploring the molecular mechanisms underlying our observations.